PERILAKU PEMBERIAN KAPSUL VITAMIN A IBU NIFAS OLEH BIDAN PUSKESMAS DIWILAYAH DINAS KESEHATAN KOTA SEMARANG - Intan NugraheniHasanah (Universitas Duta Bangsa Surakarta, 2015)
LessVitaminAprevention programinIndonesiahas beenimplementedin theclinicamong others bymidwiveswithvitamin A supplementationpostpartum mothers. Postnatalcare coveragein Central JavaProvincewas93.97% with thelowest coverageisthe city of Semarang(64.68%). The purpose of this study is to analyze the behavior of vitamin A postpartum mothers by midwives by Midwifeinthe areaof Semarang CityHealth Office.This research isquantitativeexplanationto thecross-sectional approach. Subjects wereallmidwivesclinic(136 woman) in the city ofSemarang. Data was collected throughobservationandquestionnaireKIAbookusing astructured questionnaire. Bivariate analysisperformedbychisquaretest, performedbymultivariatelogistic regression.Resultsof the analysis showedrespondentsaged median 34.5yearswith tenure16years. Much of the behaviorof vitaminApostpartum mothersaccording to the standard 52.2%, goodknowledge ofthe respondents 71.3%,the role ofsupervisorysupport 61.8%. There is a relationshipbetweenage, years of serviceto the behavior ofvitaminApostpartum mothers. There is norelationshipbetweenknowledge and supervisingroleinthe behavior ofvitaminApostpartum mothers. Health Department should be socialization toward of vitamin A postpartum midwifeabout the timingandthe benefits ofvitamin A supplementationonmaternalpostpartumpostpartum mothersandroutinefacilitativesupervisiontomidwives.Keywords: Vitamin A Capsules, Childbirth, Midwife